Ecological Assessment of the Native Flora of Matta Kharari Village, Swat, Khyber Pakhtunkhwa, Pakistan - Shima Habib; Lal Badshah; Ishtiaq Ahmad; Waqar Ahmad; Abdullah; Shujaul Mulk Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Plant species composition, diversity and distribution is a hierarchical expression of vegetation determined by different environmental factors. A study was conducted to document the floristic composition and biological spectrum of plant species of the Matta-Kharari region, Swat. The region has not been ecologically explored yet. We used quantitative ecological techniques for sampling plant species. Sixty-seven quadrats of 1x1 m2 for herbs, 5x5 m2 for shrubs and 10x10 m2 size for trees were established. Plant species data were analyzed using multivariate statistical techniques. We evaluated 76 plant species belonging to 42 families. Asteraceae and Rosaceae were the leading families with 8 species each, followed by Ranunculaceae, Lamiaceae and Moraceae with 4 species each. Among life form classes i.e., geophytes were dominant (13 species, 17.10 %), followed by therophytes (12 species, 15.87 %), nanophanerophytes (11 species, 14.47 %), and chamaephytes (10 species, 13.58 %). Moreover, Mesophylls (36.84 %) were the dominant leaf spectra class followed by nanophyll (30.26 %), microphyll (27.63 %), and megaphyll (2.63 %). The two-way cluster analysis classified the vegetation into three clusters. The detrended correspondence analysis shows the distribution of plants in a mixed array because the locations explored are characterized by similar climatic factors and vegetation. We elucidate that the variation in climatic factors and topography brings variation in vegetation. Understanding these responses at the life form and leaf spectra level will provide a better understanding and knowledge that how plant species and their communities or associations respond to changes in climate in the future. The current study could be utilized as a baseline for large-scale studies in the future.